Analysis of Sexual Violence in Online Media Against Millennial Generation Muslim Women - Rahmawati, Ema (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine and analyze cases of sexual violence in the media experienced by millennial Muslim women. The research method used is a qualitative descriptive approach with a feminist perspective with a phenomenological approach. The objects of research studied include social media in the form of WhatsApp, Twitter, Instagram, and Facebook. Meanwhile, millennial Muslim women who are active on social media and have experienced cases of online-based sexual violence are the subjects of the study. Data sources were obtained through observation by distributing questionnaires. Data analysis was carried out by reviewing, organizing data and finding research results that can be reported systematically. The results of the study show that millennial Muslim women have experienced many cases of sexual violence on various social media, including sexting (sex texting), to threats to spread pornographic videos. Anonymity on social media allows perpetrators to feel freer to express themselves, so cases of sexual violence on online media are more likely to occur. Among the prevention efforts offered by researchers are social media campaigns about the dangers of online sexual violence and being wise in using social media as well as early sex education